Effect of Treatment Sequencing on the Tumor Response to Combined Treatment With Ultrasound‐Stimulated Microbubbles and Radiotherapy. (11th June 2020) - Klein, Jonathan; Tran, William; Lai, Priscilla; Al‐Mahrouki, Azza; Giles, Anoja; Czarnota, Gregory J.
Abstract : Objectives: To investigate whether timing and sequencing of ultrasound‐stimulated microbubbles (USMBs) and external beam radiotherapy (XRT) affect the treatment response in a preclinical prostate cancer model. Methods: Prostate cancer xenografts were treated with ultrasound‐stimulated lipid microspheres before and after 8‐Gy XRT. Treatments were separated by 0, 3, 6, 12, and 24 hours, with 5 tumors per group. Tumor effects were evaluated by microvessel density (measured by CD31 staining), cell death (terminal deoxynucleotidyl transferase deoxyuridine triphosphate nick end‐labeling and hematoxylin–eosin staining), and hypoxia (carbonic anhydrase 9 staining). Results: Administering USMBs 6 hours before XRT showed the maximum treatment effect using all 3 assays. At this time, the mean cell death index ± SD was 36% ± 10%, compared with 19% ± 4% for no separation between USMB treatment and XRT; the microvessel density was 9 ± 3 counts per field (19 ± 5 without separation); and the percentage of hypoxic cells was 10% ± 5% (21% ± 4%). The observed treatment effect was greater with USMBs before XRT than when administering XRT first, but these differences were not statistically significant. Conclusions: The maximum tumor effect was observed with USMBs delivered 6 hours before XRT. The sequencing of treatment did not have a significant effect on the tumor response.